(untitled) (San Francisco, Calif., 2008)
Molecular Biology of the Gene retains the distinctive character of earlier editions that has made it the most widely used book in molecular biology. Twenty-two concise chapters, co-authored by six highly respected biologists, provide current, authoritative coverage of an exciting, fast-changing discipline.
Ứng dụng công nghệ sinh học trong bảo vệ cây trồng,Công nghệ sinh học trong bảo vệ thực vật
Keywords: Molecular biology,Sinh học phân tử